Genetic and molecular regulation of colour and pungency in Hot pepper (Capsicum spp): A review - MANGAL, MANISHA; SRIVASTAVA, ARPITA; TOMAR, B S (The Indian Journal of Agricultural Sciences, 2018)
Chilli (Capsicum spp) is an important horticultural crop both from its economic importance point of view and its nutritional value. It is an excellent source of natural colours and nutraceutical compounds. Chilli is a popular food ingredient in many parts of the world because of its two special attributes pungency and colour. It is pungent because of capsaicinoid alkaloids which get accumulated in the placenta of maturing fruits. The most abundant components of these compounds are capsaicin and dihydrocapsaicin. Capsaicinoids give a peppery flavour to meals and have various other interesting properties and applications such as antioxidant, antimutagenic and antitumoral activities. In addition, it possesses a number of pigments which impart it different colours. Various molecular explanations have been proposed for specific colour and pungency in peppers. An understanding of the regulation of the carotenoid as well as capsaicinoid pathways is necessary to manipulate these two traits in chilli. This article deals with the current state of knowledge of the molecular biology of these two traits in the genus Capsicum.